Pollution Abatement of District Hospital Ganderbal (International Journal of Innovative Research in Engineering & Management, 2023)
Ganderbal town having a population of  28233 as per census 2011 is situated 18 Km north east of  Srinagar city. There is no existing sewerage system in the  city.Ganderbal District Hospital is under construction at  Duderhama, Ganderbal. The total capacity of this hospital  is 200 beds but presently working 100 beds only.  Ganderbal District hospital has three story building and  there are three blocks emergency, labs & OPD. The total  area of hospital is 135601 Sq.ft. Nearby this hospital a  two storied building nursing college and a mental hospital  which are also under constructed. The sanitation system not only deals with environmental  issues but here also links to religious activities throughout  the town, many religious activities are carried out in the  Manasbal Lake area. The rehabilitation of the river will  make a positive impact on attracting tourists with a  comfortable and sensible culture at the same time. It is  not at all easy to evaluate the benefits of providing a  proper sanitation system and waste disposal systems in  public health, the importance of which is well known.  Where wastewater management is inadequate, the cost of  healthcare-associated with water-borne diseases is a  challenge for public economic resources.
Keywords: Water Quality; Water Quality Analysis; Ganderbal; Kashmir